KEMAMPUAN MAHASISWA ANGKATAN 2018 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNRI DALAM MENENTUKAN ISI TEKS DESKRIPSI - Fazri, Muhammad Ismail; Hadriana, Hadriana; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study describes and explains the ability of 2018 students of the Japanese language education program FKIP UNRI in determining the contents of the description text. The purpose of this study was to determine the ability of 2018 students in determining the contents of the description text. In this study the authors used a descriptive research method by using a quantitative approach. Test processed using Microsoft Excel. Test results in class 2018 acquired the average student’s ability to determine the content of the description text by 74,28 and an average percent is 70,6%. That value falls into a good category because it’s in the 71-90 range. Thus, the ability of 2018 students of the Japanese language education program FKIP UNRI to determine the contents of the description text is good.Key Words: Description Text, Dokkai